Reaction submaxillary salivary glands on the use of drinking water with multicomponent composition - A Y Kozlova; R S Matveev; P B Karyshev; S P Sapozhnikov (RUDN Journal of Medicine, 2009)
The article describes the study of reaction Wharton's salivary glands on the use of animals drinking water with different qualitative composition. Revealed that the high concentration of silicon increases the excretory activity of serous division, without a significant effect on the mucous membrane. Then, as high concentrations of calcium increased as the excretory and secretory activity of mucous and serous departments.